2012
DOI: 10.4049/jimmunol.1200892
|View full text |Cite
|
Sign up to set email alerts
|

Lipocalin 2 Deficiency Dysregulates Iron Homeostasis and Exacerbates Endotoxin-Induced Sepsis

Abstract: Various states of inflammation, including sepsis, are associated with hypoferremia, which limits iron availability to pathogens and reduces iron-mediated oxidative stress. Lipocalin 2 (siderocalin, 24p3) plays a central role in iron transport. Accordingly, Lipocalin 2-deficient mice (Lcn2KO) exhibit elevated intracellular labile iron. Here we report that LPS-induced systemic Lcn2 by 150 fold in WT mice at 24h. Relative to WT littermates, Lcn2KO mice were markedly more sensitive to endotoxemia, exhibiting eleva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
99
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 116 publications
(109 citation statements)
references
References 56 publications
8
99
0
2
Order By: Relevance
“…In accordance with our data, Zhang et al reported that LCN2 reduced the LPStriggered induction of cytokines by RAW264.7 macrophages (24). During completion of this manuscript, another group reported enhanced levels of LPS-induced proinflammatory cytokines secreted by LCN2-deficient peritoneal macrophages and BMDMs as compared with WT cells (42). However, in contrast to our data, this report also showed increased IL-10 releases by Lcn2 -/-peritoneal macrophages, which might be due to differences specific to macrophage subset or the fact that we focused on S. pneumoniae.…”
Section: Discussionsupporting
confidence: 76%
“…In accordance with our data, Zhang et al reported that LCN2 reduced the LPStriggered induction of cytokines by RAW264.7 macrophages (24). During completion of this manuscript, another group reported enhanced levels of LPS-induced proinflammatory cytokines secreted by LCN2-deficient peritoneal macrophages and BMDMs as compared with WT cells (42). However, in contrast to our data, this report also showed increased IL-10 releases by Lcn2 -/-peritoneal macrophages, which might be due to differences specific to macrophage subset or the fact that we focused on S. pneumoniae.…”
Section: Discussionsupporting
confidence: 76%
“…Elevated serum NGAL concentrations in sepsis could be attributed to the systemic launch of different inflammatory mechanisms activating local or distant neutrophils, macrophages, and other immune cells, dampening the inflammatory response (18). A major mechanism of de novo upregulation involves fundamental upstream inflammatory pathways, including signaling via Toll-like receptor 4 activated by lipopolysaccharide (19).…”
Section: Discussionmentioning
confidence: 99%
“…However, studies also showed that LCN2 can regulate the intracellular iron concentration and LCN2 deficiency can increase the cellular iron levels in sepsis. 30 Thus, the role of LCN2 in iron transport still need further study.…”
Section: Discussionmentioning
confidence: 99%